Hubungan Bauran Pemasaran (Marketing Mix) Dengan Loyalitas Pelanggan: Systematic Review - Leawaty, Leawaty; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
Marketing activities in the business era are now an important factor for maintaining and developing a business. The higher the level of competition in the business, requires management to innovate in maintaining its customers. This activity is to create loyal customers. Customer loyalty is very important for the continuity of a business. To find out the marketing mix relationship with customer loyalty. Preferred Reporting Items for Systematic Reviews and Meta Analyzes (PRISMA) are evidence-based methods for conducting systematic reviews. Based on the results of the research at the Pulmo Clinic of Paru Batu Hospital, several conclusions can be obtained that all elements of the marketing mix (product, price, place, promotion, staff, process, and physical evidence) are not all positive effects on patient loyalty. Product and place variables do not have an influence on patient loyalty, while other variables namely price, promotion, staff, process and physical evidence have an influence on patient loyalty. Elements of physical evidence and prices have the most dominant influence on patient loyalty among other elements in the marketing mix. In Siloam Manado Hospital there is no significant relationship between service products and outpatient loyalty and there is a significant relationship between service prices, service places, service promotion, service personnel, service processes, physical evidence of services, and service facilities with outpatient loyalty. The service personnel variable is the most dominant variable towards outpatient loyalty. From the results of research at the Prodia Palu Clinical Laboratory, it was found that there was a relationship between product, promotion, process and physical evidence with customer loyalty. And there is no relation between price, location / place and people with customer loyalty. At Awal Bros Pekanbaru Hospital there are still shortcomings that affect consumers for outpatient treatment, and there is the problem of expensive medical expenses. The existence of a convoluted procedure when consumers want medical treatment on an outpatient. Physical evidence indicators are indicators that have the highest value. Research about the marketing mix can be done and researchers can make improvements from the marketing mix which is the independent variable that will be investigated or continue this research in order to use other independent variables that can measure patients' decisions in doing treatment. Thus improvements can be made to design marketing strategies for hospitals.